2015
DOI: 10.1093/hmg/ddv283
|View full text |Cite
|
Sign up to set email alerts
|

SMN expression is required in motor neurons to rescue electrophysiological deficits in the SMNΔ7 mouse model of SMA

Abstract: Proximal spinal muscular atrophy (SMA) is the most frequent cause of hereditary infant mortality. SMA is an autosomal recessive neuromuscular disorder that results from the loss of the Survival Motor Neuron 1 (SMN1) gene and retention of the SMN2 gene. The SMN2 gene produces an insufficient amount of full-length SMN protein that results in loss of motor neurons in the spinal cord and subsequent muscle paralysis. Previously we have shown that overexpression of human SMN in neurons in the SMA mouse ameliorates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 102 publications
3
44
0
Order By: Relevance
“…Restoration of SMN solely in motor neuron or reduction of SMN solely in motor neurons does not markedly alter the survival of these animals (Martinez et al, 2012; McGovern et al, 2015). Furthermore, there is rescue of both electrophysiological activity and innervation status of skeletal muscle when replacing SMN solely in motor neurons (Martinez et al, 2012; McGovern et al, 2015). Thus, rescue of SMN levels in motor neurons does not correlate with survival.…”
Section: Discussionmentioning
confidence: 91%
“…Restoration of SMN solely in motor neuron or reduction of SMN solely in motor neurons does not markedly alter the survival of these animals (Martinez et al, 2012; McGovern et al, 2015). Furthermore, there is rescue of both electrophysiological activity and innervation status of skeletal muscle when replacing SMN solely in motor neurons (Martinez et al, 2012; McGovern et al, 2015). Thus, rescue of SMN levels in motor neurons does not correlate with survival.…”
Section: Discussionmentioning
confidence: 91%
“…However, whether or not MN deafferentation modifies cell death in SMA is not clear, and may, in fact, be a consequence of primary MN pathology [61,101,102]. In this regard, it has been recently reported that SMN deficiency results in intrinsic changes in the electrophysiological properties of MNs [103], and that replacement of SMN only in MNs is necessary and sufficient to restore the functional deficits of motor units [104]. These findings suggest that adequate levels of SMN in MNs are crucial to avoid the dysfunction and subsequent degeneration of MNs.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that muscle and nerve may be independently affected by SMN deficiency [17,107], and muscle has only a minor impact on SMA pathogenesis. Indeed, several studies have reported that improvements in skeletal muscle and NMJ morphology and physiology, after SMN replacement in MNs, do not result in a significant increase in survival [61,82,101,104,108,109]. Moreover, it has been recently shown that low levels of SMN in muscle are sufficient for its normal function, and muscular replacement of SMN does not modify the lifespan of SMA [110].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have focused on the role of the muscle, glial cells, and motoneurons themselves in the overall function of the motor units in SMA. Recently, the glial-specific restoration of SMN in mice with reduced SMN levels was found to be necessary to restore part of the motor unit function in a severe mouse model (59). In our study, peripheral administration of an ASO that rescues the SMA-like phenotypes of the NMJ and motor unit coincides with a better correction of SMN2 splicing in the muscle than in the spinal cord and to a greater increase of SMN protein in the heart than in the brain or the spinal cord.…”
Section: Discussionmentioning
confidence: 99%